The Barbarism of Reason : Max Weber and the Twilight of Enlightenment - Maley, Terry; Horowitz, Asher, 1950- (Book collections on Project MUSE., 1994)
The recent renewal of interest in Max Weber evidences an attempt to enlist his thought in the service of a renewed dream of Enlightenment individualism. Yet he was the first twentieth-century thinker to fully appreciate the pervasiveness and ambiguity of rationalization which threatened to undermine the hopes of the Enlightenment.Asher Horowitz and Terry Maley present a collection of essays tracing the contemporary significance of Weber's work for the tradition of Enlightenment political thought and its critiques. In its critical inquiry into Weber's thought, The Barbarism of Reason continues the exploration of the limits and prospects of politics in a rationalizing society.The first section comprises a set of both historical and philosophical reflections on the political implications of Weber's central concepts such as disenchantment, rationality, and affectivity, the historical understanding, meaning, and domination. The second section examines the institutional and historical context that framed Weber's inquiries into structures of the modern mode of domination, as well as his understanding of the nature of the modern state. Among the topics broached are Weber's strategic intervention into the development of the liberal theory of the state as well as a critical examination of the theoretical and pre-theoretical roots of his construction of the subject. Another of the essays reveals the schizophrenic structure of modern subjectivity. The third and last section attempts to trace the vicissitudes of Weber's seminal problems concerning rationalization, power, and disenchantment through some of the most important responses to his work in the twentieth century.